A Study on Factors Influencing the Institutional Care of Children with an Intellectual Disability in the Western Province of Sri Lanka - Atukoralage, Thamarika Harshani (Curtin University, 2024)
This study explored the factors influencing institutional care for children with intellectual disabilities in Sri Lanka, applying Bronfenbrenner’s ecological systems theory. Using a mixed-methods sequential explanatory approach, it identified interconnected family, economic, environmental, and societal challenges. Findings highlighted the importance of enhancing family support, community-based services, and policies to promote safe family living. Insights contribute to sustainable deinstitutionalisation programs across Sri Lanka.